High-quality de novo assembly of the Eucommia ulmoides haploid genome provides new insights into evolution and rubber biosynthesis. (1st November 2020) - Li, Yun; Wei, Hairong; Yang, Jun; Du, Kang; Li, Jiang; Zhang, Ying; Qiu, Tong; Liu, Zhao; Ren, Yongyu; Song, Lianjun; Kang, Xiangyang
Abstract: We report the acquisition of a high-quality haploid chromosome-scale genome assembly for the first time in a tree species, Eucommia ulmoides, which is known for its rubber biosynthesis and medicinal applications. The assembly was obtained by applying PacBio and Hi–C technologies to a haploid that we specifically generated. Compared to the initial genome release, this one has significantly improved assembly quality. The scaffold N50 (53.15 MB) increased 28-fold, and the repetitive sequence content (520 Mb) increased by 158.24 Mb, whereas the number of gaps decreased from 104, 772 to 128. A total of 92.87% of the 26, 001 predicted protein-coding genes identified with multiple strategies were anchored to the 17 chromosomes. A new whole-genome duplication event was superimposed on the earlier γ paleohexaploidization event, and the expansion of long terminal repeats contributed greatly to the evolution of the genome. The more primitive rubber biosynthesis of this species, as opposed to that in Hevea brasiliensis, relies on the methylerythritol-phosphate pathway rather than the mevalonate pathway to synthesize isoprenyl diphosphate, as the MEP pathway operates predominantly in trans -polyisoprene-containing leaves and central peels. Chlorogenic acid biosynthesis pathway enzymes were preferentially expressed in leaves rather than in bark. This assembly with higher sequence contiguity can foster not only studies on genome structure and evolution, gene mapping, epigenetic analysis and functional genomics but also efforts to improve E. ulmoides for industrial and medical uses through genetic engineering.